Synthesis of 4- to 7-membered Heterocycles by Ring Expansion Aza-, oxa- and thiaheterocyclic small-ring systems - D'hooghe, Matthias; Ha, Hyun-Joon.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
Ring expansions of non-activated aziridines and azetidines -- Ring expansions of activated aziridines and azetidines -- Ring expansions of azirines and azetines -- Ring expansions of beta-lactams and beta-(thio)lactones -- Ring expansions of oxiranes and oxetanes -- Ring expansions of thiiranes and thietanes.
Keywords: Chemistry, Organic; Medicinal chemistry; Biotechnology; Organic Chemistry; Medicinal Chemistry; Chemical Bioengineering